Dengue Serotypes In Manipur – Findings From A Retrospective Analytical Study In A Tertiary Care Hospital - Laitonjam Anand Singh; Thingujam Suson; Chongtham Geeta Chanu; Khuraijam Ranjana Devi; Heigrujam Rebachandra Singh (International Journal of Medical Research and Review, 2024)
Objectives: As a part of on-going research programme on vector-borne viral diseases especially on Dengue, a retrospective analytical study on the occurrence and distribution of Dengue virus serotype(s) in the state of Manipur – a small state situated in the north eastern region of the Indian subcontinent was carried out at Viral Research & Diagnostic Laboratory (VRDL), Department of Microbiology, Regional Institute of Medical Sciences (RIMS), Imphal which is a tertiary care hospital. Materials & Methods: A total of 914 blood samples from clinically dengue suspected patients were screened for the presence of Dengue infection by adopting ELISA (IgM) technique during the period from 01/06/2022 to 02/12/2022. Further, anti-Dengue IgM antibody positive samples having high Optical Density (OD) value(s) were selected and subjected to RT PCR to determine the serotype(s) of Dengue virus. Results: Of the 914 blood samples examined for the presence of Dengue infection, 111 (12.14%) were found positive for anti-Dengue IgM antibody indicating acute infection of Dengue virus. Of the positive patients, there were 56 (50.45%) males and 55 (49.54%) females. The sex difference was found to be statistically insignificant (।z।CV = 0.016; z ˂ 1.96; P ˂ 0.05). Predominant clinical features observed among the Dengue confirmed patients included – fever (74%), headache (19%), arthralgia / joint pain (9%), myalgia (6%) and vomiting (6%) respectively. Haemorrhagic manifestation was observed in only one (01) patient. Only three (03) Dengue positive patients had the history of travelling outside the state. The study revealed that while circulation of three (03) Dengue virus serotypes, namely DENV – 1, DENV – 2 & DENV – 3 were observed in the Tengnoupal district, the circulation of two Dengue virus serotypes i.e., DENV – 1 & DENV – 2 were evident in Imphal West & Bishnupur districts respectively. The present study also reveals the occurrence of Dengue virus serotype – 1 (DENV - 1) in Churachandpur district. Conclusion: The present study reveals the circulation / distribution of three Dengue virus serotypes namely, DENV – 1, DENV – 2 and DENV – 3 among the studied samples. Findings from this pilot study stresses the need for continuing more in-depth studies among the population of the state towards identifying serotypes endemic/prevalent in the different districts of the state. Keywords: Dengue virus, Dengue IgM ELISA, Dengue serotype (RT PCR)